Giving presentations - Billingham, Jo (Oxford University Press, 2003)
A book of practical advice and useful tips on how to give clear and effective presentations. This lively, accessible, and illustrated guide is divided into two sections. The first provides comprehensive advice on writing, rehearsing, and giving your presentation, both as an individual or as part of a team. The second section contains a useful presenter's toolkit to inspire and build confidence and help with the tricky task of presenting across languages and cultures.